Simultaneous Management of Otogenic Brain Abscess and Suppurative Otitis Media: Retrospective analysis - Shrestha, Ram K; Sedain, Gopal; Sharma, Mohan R; Shilpakar, Sushil K; Pradhananga, Amit B; Kafle, Prakash; Rajbhandari, Binod (Nepal Journal of Neuroscience, 2016)
Intracranial complications of Chronic Suppurative Otitis Media(CSOM) are common. Brain abscess is the commonest intracranial complication. Traditionally, life threatening brain abscess was managed first and the causative otitis dealt later. However, with the aim of dealing with both at the outset, we have started treating these problems in the same anesthesia setting. Retrospective analysis of the consecutive patients treated simultaneously is presented. Nepal Journal of Neuroscience 13:19-22, 2016